Rattus hoogerwerfi Chasen 1939 - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Rattus hoogerwerfi Chasen, 1939. Treubia, 17(3):496. TYPE LOCALITY: Indonesia, W Sumatra, Aceh, Gunung Leuser, Blang Kedjeren, 2900 ft. DISTRIBUTION: Known only from between 2900 and 9300 ft in foothills and upper slopes of Gunung Leuser, Sumatra (see map in Musser, 1986). COMMENTS: Very distinctive and possibly not a member of Rattus. Morphology and comparisons with other species documented by Musser and Newcomb (1983) and Musser (1986). Although phylogenetic affinities with species of Rattus from Sulawesi, the Philippines, and Christmas Island have been claimed by Miller (1942), and with R. korinchi by Chasen (1939), no compelling evidence links R. hoogerwerfi with any other species (Musser, 1986). Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 653, DOI: 10.5281/zenodo.7353098